Creative People and Its Manifestation in Creative Industry - Astuty, Eriana; Harding, Diana (International Journal of Psychosocial Rehabilitation, 2020)
Creativity, born from the creative people’s idea as a result of the use of science/culture/technology/ experience. Empirically, creative people in Indonesia's creative industries become urgent to be developed. Research objects are creative people and entrepreneurial orientation. This research aimed to describe the creative people’s and entrepreneurial orientation’s characteristics; to confirm the manifestation of creative people as well as entrepreneurial orientation; finally to verify the trigger of the emergence of creative people. This research using descriptive and verification methods with SPSS20 and SmartPLS3 as statistical tools. Verificatively, confirmed that the entrepreneurial orientation has high effect to trigger the emergence of creative people (81%), the strength of the predictive model is high (65.8%), the effect size f2=1.924 which means that entrepreneurial orientation has large influence in generating creative people; Q2>0 indicates this model is declared relevant in predicting. This finding is important because creative people are renewable resources needed to produce creativity and innovation as the basis of the development of creative industries.